Teaching chemistry in the metaverse: the effectiveness of using virtual and augmented reality for visualization - Amirbekova, Elmira; Shertayeva, Nailya; Mironova, Ekaterina (Frontiers in Education, 2024)
Introduction The metaverse is a promising platform for learning that all participants in the teaching and learning process may find appealing. This study aims to investigate the effectiveness of using metaverse-related visualization technologies, such as Virtual Reality (VR) and Augmented Reality (AR), in teaching chemistry. Methods The study has an experimental research design and uses the following tools to collect data: Dombrovskaya’s Motivation for Learning Scale, the SAMOAL Questionnaire, and the Self-management Questionnaire. The study sample includes 236 first-year undergraduate students studying chemistry at the Faculty of Natural Sciences. Results Results suggest that the integration of immersive VR/AR technologies in chemistry education signifies the beginning of a metaverse transition; the process, however, is in its early stages. Discussion The study concludes that immersive VR/AR technologies have an advantage over traditional programs in terms of motivation and competence development. Future research can investigate the impact of VR/AR technologies on students’ anxiety and build a model for predicting student achievements in the metaverse-based chemistry classroom.